Use of a rainbow trout (Oncorhynchus mykiss) intestinal in vitro platform to evaluate different diets - Camin, F.; Verdile, N.; Chacon, M.A.; Løkka, G.; Peggs, D.; Tandler, A.; Bitan, A.; Kortner, T.M.; Fontanillas, R.; Brevini, T.A.L.; Gandolfi, F. (Frontiers in Marine Science, 2025)
Fish oil and fish meal increase the nutritional value of fish meat for human consumption. The aquafeed industry constantly assess new ingredients to improve flexibility and sustainability of the raw materials. The search for alternative ingredients could be helped by the development of an in vitro platform that could screen promising candidates in a fast and cheap way. Aim of this paper is to determine if a platform using rainbow trout intestinal cell lines can discriminate the functional differences of feed formulations characterized by contrasting properties. We compared a reference diet, rich in fish meal (FM), with diets with high inclusion of either soybean meal (SBM) or feather meal (FTHM). Before exposing the diets to the in vitro platforms, pellets were exposed to gastric and intestinal RT enzymes to extract the bio-accessible fraction (BAF). Rainbow trout cell lines, derived from the proximal (RTpiMI) or distal (RTdiMI) intestine were exposed to BAFs for 21 days. Barrier integrity and functionality were assessed measuring transepithelial electrical resistance, evaluating cell morphology and determining alanine aminopeptidase enzyme activity. Results showed that SBM disrupted the epithelial barrier formed by cells of the proximal but not the distal intestine. However, this effect was reversible, as barrier integrity was fully restored once the SBM was removed. In contrast, FTHM induced a progressive cell proliferation in both proximal and distal intestinal cell line. This milder effect could mimic an inflammatory response, that was induced also by the FM, possibly due to the lack of mucus in vitro, leaving intestinal cells without a physiological protection. In conclusion, in vitro trials showed a variable range of responses to the diets depending on the intestinal region of origin of the cells, providing a functional ranking of the diets. Moreover, the ability of the proximal intestine cells to fully recover from the initial damage caused by SBM suggests that this platform could also be used to identify target molecules that can mitigate the effects of the anti-nutritional factors present in raw materials such as SBM.